Cross-Cutting Learning from Evaluations: CGIAR Excellence in Breeding and Big Data in agriculture Platforms - CGIAR Independent Advisory and Evaluation Service (CGIAR Independent Advisory and Evaluation Service, 2022)
This cross-cutting brief analyzes learning and recommendations by five themes (governance, gender, partnerships, people, and capacities, and monitoring, evaluation, and learning) across the CGIAR Excellence in Breeding (EiB) Platform and Platform for Big Data in Agriculture evaluations. Lessons from the brief are intended to be applied across CGIAR's portfolio and to inform interventions outside CGIAR that pursue similar objectives